Massive Ascites Complicating Pre-eclampsia - Ma-Lee Ko (Taiwanese Journal of Obstetrics & Gynecology, 2005)
Objective: We report a case of a woman 27 weeks into her pregnancy with severe pre-eclampsia complicated by severe ascites diagnosed using ultrasonography and managed with paracentesis. Case Report: A 41-year-old woman, gravida 5, para 2, abortus 2, was referred from a prenatal clinic due to pre-eclampsia and complaints of headaches, blurred vision, and abdominal discomfort. In spite of treatment with hydralazine and magnesium sulfate and an albumin infusion, she developed orthopnea and abdominal distension. During ultrasound, severe maternal ascites of about 2,000 mL was discovered. Paracentesis was performed at 27+3 weeks. After the procedure, there was significant improvement in the patient's symptoms. However, complaints of abdominal distension and difficulty breathing recurred in week 31. Repeat paracentesis was performed followed by administration of corticosteroid for fetal lung maturation. At 31+3 weeks, the baby was delivered by cesarean section due to progressive toxemia and intrauterine growth retardation. During the operation, 1,500 mL of ascitic fluid was aspirated from the pelvic cavity. A female neonate was delivered with a birth weight of 1,020 g and Apgar scores of 6 and 8 at 1 and 5 minutes, respectively. At the 6-week follow-up, the patient was well and normotensive, and the baby was discharged from the neonatal intensive care unit. Conclusion: Clinicians should be aware of the possible presence of ascites in patients with severe pre-eclampsia. If the hypertension is controlled and the fetus is healthy, abdominal paracentesis without pregnancy termination is an efficacious procedure for the management of massive ascites complicating severe pre-eclampsia.